2012
DOI: 10.1024/0301-1526/a000222
|View full text |Cite
|
Sign up to set email alerts
|

Varicose veins are a risk factor for deep venous thrombosis in general practice patients

Abstract: There are strong associations between VV and DVT in a general practice population with documented VV. Special medical attention is required for patients with VV, a history of previous venous thromboembolism, comorbid malignancy, and recent hospital discharge, particularly those with a combination of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 0 publications
6
48
0
1
Order By: Relevance
“…It is questionable, if many of DVTs occurring after 30 days can be directly attributed to the patients' VV treatment; more likely this represents an inherent predisposition of varicose veins to DVT formation. This would be consistent with the fi nding that primary care patients with VV have an increased risk of DVT compared to patients without VV [15], and that treating some or all of the varicosities does not seem to eliminate this risk. Understanding this phenomenon in its entirety requires knowledge of the incidence of the DVT in patients with varicose veins who are managed conservatively, which at present does not exist.…”
Section: Number Of Vtes By Yearsupporting
confidence: 77%
“…It is questionable, if many of DVTs occurring after 30 days can be directly attributed to the patients' VV treatment; more likely this represents an inherent predisposition of varicose veins to DVT formation. This would be consistent with the fi nding that primary care patients with VV have an increased risk of DVT compared to patients without VV [15], and that treating some or all of the varicosities does not seem to eliminate this risk. Understanding this phenomenon in its entirety requires knowledge of the incidence of the DVT in patients with varicose veins who are managed conservatively, which at present does not exist.…”
Section: Number Of Vtes By Yearsupporting
confidence: 77%
“…Conversely, VVs may develop as a part of post‐thrombotic syndrome following DVT. Müller‐Bühl et al analyzed ICD coding‐based primary care register data and demonstrated that DVT was nearly six times more frequent among VVs patients than among individuals without VVs . Based on this evidence, we cannot exclude the possibility of some bias in “23andMe” and the UK Biobank studies.…”
Section: Discussionmentioning
confidence: 94%
“…Varicose veins, caused by reduced venous blood flow, affect a different part of the venous system but represent a DVT-associated disease, that, at least in its severe form, presents a risk factor for DVT. 31 Similar to thrombotic deep veins, human varicose veins often contain a greater number of inflammatory cells, including T cells. 32 To examine the impact of blood flow reduction on T-cell recruitment in the human venous system, we analyzed the composition of the T cell infiltrate in varicose veins compared with peripheral blood.…”
Section: Human Varicose Veins Predominantly Contain T Em Cellsmentioning
confidence: 99%